2020
DOI: 10.3390/ani10040615
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Selenium Sources on Meat Quality and Shelf Life of Fattening Pigs

Abstract: The aim of this study was to evaluate the effects of different Se sources on the meat quality and shelf life of fattening pigs. The control diet was supplemented with 0.3 mg/kg of Se from sodium selenite (SS), and experimental diets included 0.3, 0.3 and 0.15 + 0.15 mg/kg of Se from Se-enriched yeast (SY), selenomethionine (Se-Met) and SS + Se-Met, respectively. The results showed that using organic Se or Se + Se-Met in fattening pigs’ diet could increase average daily gain (ADG) (p < 0.05), decrease F/G (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…The differences in total Se deposition between the muscle and liver may perhaps be due to the different roles they play in Se metabolism. The liver is a main organ for selenoprotein synthesis, Se metabolism and Se transport to other tissues, while the muscle is a major organ for Se storage [ 59 , 60 ]. Selenium plays an important role in antioxidant activity, as it can prevent peroxidation and protect the immune cells and tissues from damage caused by the free radicals [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The differences in total Se deposition between the muscle and liver may perhaps be due to the different roles they play in Se metabolism. The liver is a main organ for selenoprotein synthesis, Se metabolism and Se transport to other tissues, while the muscle is a major organ for Se storage [ 59 , 60 ]. Selenium plays an important role in antioxidant activity, as it can prevent peroxidation and protect the immune cells and tissues from damage caused by the free radicals [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Genetics and environmental factors, including the feeding strategies, affect the carcass quality traits directly [ 53 ]. Although no significant difference was observed in back-fat thickness of both treatments, Zhang et al [ 54 ] stated that O-Se can provide some vitamins, amino acids, protein, and other nutrients for the body and can cause subsequent increase in fat accumulation. Similar to that, Choi et al [ 55 ] also reported significant differences in the carcass length and back-fat thickness of pork meat obtained from animals fed stevia and charcoal-supplemented diets.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the average microbial count tended to decrease in S and O-Se treatment during the refrigerated storage period, possibly because the GSH-Px enzymatic activity can eradicate harmful lipid peroxide and H 2 O 2 from organisms, resulting in less favorable reproductive conditions for microbes. Hence, the microbial population tends to decrease gradually [ 54 ]. Moreover, antioxidant molecules in stevioside can scavenge free radicals that influence the retarded muscle oxidation process and reduce the microbial flora content in meat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selenium (Se) could catalyze hydrogen peroxide reduction, protect cell membrane and reduce oxidative damage [1]. It was a necessary micronutrient for health, growth, reproduction and immunity of humans and animals [2][3][4][5][6][7]. In a certain concentration range, with the increase of biological effects of selenium in the body, the concentration of reactive oxygen free radicals gradually decreases, which played an important role in the formation and defense of oxidative stress [8,9].…”
Section: Introductionmentioning
confidence: 99%